Psychometric Properties of the Nine-Item Problematic Internet Use Questionnaire (PIUQ-9) in a Lithuanian Sample of Students - Burkauskas, Julius; Király, Orsolya; Demetrovics, Zsolt; Podlipskyte, Aurelija; Steibliene, Vesta (Frontiers in Psychiatry, 2020)
Objectives: To date, there is no reliable instrument which could be used to assess problematic Internet use (PIU) in Lithuania. The nine-item Problematic Internet Use Questionnaire (PIUQ-9) previously validated in multiple countries, could be a potential tool for measuring PIU severity. The main objective of the present study was to explore the psychometric properties of the Lithuanian version of the questionnaire. Methods: A total of 272 students (17% men, mean age 27±9 years) completed the PIUQ-9, the Patient Health Questionnaire (PHQ) and answered questions about the impairment of daily functioning caused by PIU in an online survey. Results: A confirmatory factor analysis indicated that a bi-factor model with one general factor “general problem” and two-specific factors “obsession” and “neglect + control disorder” fitted the data well. The presence of a strong global factor was supported by the common variance index in the bi-factor model indicating that the “general problem” factor explained 67.7% of common variance. The multiple indicators multiple causes (MIMIC) model showed that psychiatric symptoms (β=0.25) had a moderate, while impairment due to PIU (β=0.41) had a moderate-to-strong direct effect on the factor “general problem” supporting the construct validity of the scale. Conclusion: The Lithuanian version of the PIUQ-9 has appropriate psychometric properties to be used in measuring PIU severity in student samples.